Development and implementation of a trajectory planner and a tracking controller for an autonomous vehicle - Pham, Minh Tuan. (2008)
Development and implementation of a trajectory planner and a tracking controller for an autonomous vehicle. Focuses on two major tasks of autonomous vehicle control: Trajectory Planning and Trajectory Tracking.